2017
DOI: 10.1016/j.ultsonch.2016.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of biodiesel production using dual-frequency counter-current pulsed ultrasound

Abstract: Biodiesel production from soybean oil deodorizer distillate intensified by dual-frequency counter-current pulsed ultrasound and the kinetics were studied. Results indicated that the biodiesel conversions enhanced by single-frequency were lower than those enhanced by dual-frequency. For dual-frequency, the biodiesel conversion of SMM was higher than those of SQM. The biodiesel conversion of the combination of 20/28kHz is the highest. The effects of 20/28kHz SMM on biodiesel production were studied and optimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…In a study by Fan et al [58] , by increasing the molar ratio from 3:1 to 6:1 utilizing a frequency of 40 kHz, the yield also increased. A similar study on the transesterification of soybean oil by ultrasound (20 kHz −28 kHz) reported an optimum reactant molar ratio of 8:1 [15] . Analyzing the obtained trends, one can say that the increase of yields of methyl esters due to excess methanol does not depend on the ultrasonic frequency (high or low) used in the measurement system.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In a study by Fan et al [58] , by increasing the molar ratio from 3:1 to 6:1 utilizing a frequency of 40 kHz, the yield also increased. A similar study on the transesterification of soybean oil by ultrasound (20 kHz −28 kHz) reported an optimum reactant molar ratio of 8:1 [15] . Analyzing the obtained trends, one can say that the increase of yields of methyl esters due to excess methanol does not depend on the ultrasonic frequency (high or low) used in the measurement system.…”
Section: Resultsmentioning
confidence: 72%
“…The results show that both configurations, 1 MHz and 3 MHz, achieve higher conversion levels in a shorter period within higher molar ratios. It occurs due to methanol excess that shifts the reaction equilibrium towards FAME production and increases the number of cavitation bubbles due to greater ease of cavitation in methanol than in oil [15] , [57] . Than et al [22] have reported similar results with increasing molar ratio on transesterification of canola oil with methanol using low-frequency ultrasound (20 kHz).…”
Section: Resultsmentioning
confidence: 99%
“…Yin et al . [29] discovered that dual-frequency ultrasound would produce disturbance in mediums, addressing the drawbacks of single-frequency ultrasound’s unequal volume energy consumption and directional sensitivity. Kerboua et al .…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, a escolha acertada de um insumo adequado pode contribuir para reduzir esses impactos. O biodiesel é um biocombustível de baixo valor agregado e isso dificulta sua comercialização, por isso a utilização de óleos mais baratos e não comestíveis na sua produção em grande escala é uma alternativa (BACENETTI et al, 2017;YIN et al, 2017). A Tabela 1 apresenta as principais matérias-primas utilizadas para a produção de biodiesel no Brasil.…”
Section: Matérias-primas Utilizadas Na Produção Do Biodieselunclassified